Correlation between discharge readiness and uncertainty in illness among parents with preterm infants hospitalized in NICU - TAN Jilei (中西医结合护理, 2021)
Objective To investigate the correlation between discharge readiness and uncertainty in illness among parents with preterm infants hospitalized in NICU, so as to provide a reference for clinical training. Methods Totally 75 parents with preterm infants were investigated using Readiness for Hospital Discharge Scale-Parent Form (RHDS-FM) and Parents' Perception of Uncertainty Scale-Family Member(PPUS-FM). Results The total score of uncertainty in illness and discharge readiness were (95. 73±13. 49) and (132. 04±25. 85) respectively, 54. 67%(41/75) of the parents believed that they were not ready for discharge; and the discharge readiness was negatively correlated with the uncertainty of illness (r= -0. 346, P<0. 01). Conclusion The discharge readiness and illness uncertainty of parents of premature infants are both at a moderate level, and they are closely related. The higher the discharge readiness , the lower the illness uncertainty. Therefore, medical staff should pay close attention and evaluate the discharge readiness and illness uncertainty of the parents of premature infants, and provide timely information support, especially care knowledge and plans, to change parents' abnormal cognition, and prepare premature infants and their parents for a smooth transition to the family.